Characterization of the C-terminal tail of the Arc protein. - Melissa Boldridge; Jody Shimabukuro; Keith Nakamatsu; Christian Won; Chad Jansen; Helen Turner; Lei Wang (PLoS ONE)
The activity-regulated cytoskeleton-associate protein Arc (or Arg3.1) is specifically linked to memory formation and a number of cognitive disorders, including Alzheimer's disease and schizophrenia. Since the discovery of Arc in 1995, extensive research has been conducted on the protein to identify its function and mechanisms of action, with solving the structure of Arc as a major goal. However, the Arc protein tends to self-oligomerize in vitro, and is difficult to crystallize. These properties have hindered efforts to obtain the structure of the full-length, whole protein Arc. As an alternative approach, we and others, have sought to solve the structures of various subdomain proteins of Arc, including the N-lobe, C-lobe, and capsid domain (N-lobe + C-lobe). In this study, we characterized the C-terminal tail of Arc using integrated bioinformatic and structural biology techniques. We compared the sequences of Arc proteins in different mammal species and found that the amino-acid composition in the C-terminal tail region has a significantly higher degree of variation rate than the rest of the protein. Structural prediction programs suggested that the C-terminal tail is structurally disordered. Chemical shift analysis based on solution NMR spectra confirmed that the C-terminal tail has a random coil (disordered) structure, and the tail starts from the residue D357. Furthermore, the NMR spectra showed that the C-terminal tail has minimum (if any) interaction with its neighboring capsid domain in Arc. This study fills gaps in our specific understanding of the structural nature and functional contributions of the Arc C-terminus.